Blend Modified Polymers (Polyethersulfone, Expandable Polystyrene, Polyvenylidinefluride) as a Membrane for Microbial Fuel Cell - A. Al-Taie, Zainab; Salih Shihab, Mehdi; Allami, Shrok (Al-Nahrain Journal of Science, 2021)
In this work membrane (proton exchange membrane) by using the blend polymers (polyethersulfone (PES), Expandable polystyrene (EPS), polyvenylidinefluride polymer (PVDF)) were prepared. This membrane was modified by adding organic sulfonic acid to the blend solution pre casting process, and sulfonated by dipping it in diluted sulfuric acid (H2SO4 60 %) post casting process. The sulfonation was confirmed via FTIR spectra. The sulfonated membrane was characterized by proton conductivity, ion exchange capacity (IEC), (-SO3H) content, and water uptake. Microbial Fuel Cell (MFC) is characterized by electrochemical polarization tests and power densities obtained from it used to evaluate the efficiency of the membrane in the cell.